The epidemiology of diabetes in psychotic disorders. (May 2015) - Ward, Martha; Druss, Benjamin
Summary Diabetes is highly prevalent in people with psychotic disorders, including schizophrenia and schizoaffective disorders. Exact prevalence is difficult to estimate, since diabetes is often underdiagnosed in people with psychosis. Results of several studies show that the prevalence of diabetes exceeds that in the general population, with documented prevalence in those with psychosis ranging from 1·26% to 50% across studies (median 13%). The association between diabetes and psychosis is complex and multifactorial. Many of the traditional risk factors for disease have increased prevalence in patients with psychotic disorders. In addition to these traditional risk factors, people with psychosis have unique risks that might have additive or even synergistic effects. These risks include the use of antipsychotic medication, the effects of adverse social determinants of health, and genetic loading. Despite evidence that rates of diabetes are increased in individuals with psychosis, many of these patients are not diagnosed or treated, resulting in increased diabetes-associated morbidity and mortality. Specific patient factors, provider issues, and systems-level factors contribute to the treatment gap. Interventions at both the clinical and public health levels are needed to successfully address this problem.